Bank Muamalat Indonesia Branch Kolaka Strategy in Encouraging Small and Intermediate Business in Regency Kolaka - Wahyuni, Sri; Suarni, Agusdiwana; Amanda, Meli (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is a qualitative descriptive type of research with the aim of finding out the strategy of Bank Muamalat Indonesia Kolaka branch in encouraging small and medium businesses in Kolaka district and to find out the back to back financing mechanism at Bank Muamalat Indonesia Kolaka branch in encouraging small and medium businesses in Kolaka district . The results of the research show data using interviews and data collection regarding the strategy of Bank Muamalat Indonesia Kolaka branch in encouraging small and medium businesses in Kolaka district and to find out the back to back financing mechanism at Bank Muamalat Indonesia Kolaka branch, the author draws an important conclusion, namely a business strategy that can in the form of geographic expansion, diversification, acquisition, product development, market penetration, employee rationalization, divestment, liquidation, as well as to determine and achieve organizational goals and special mechanisms that can differentiate one from another.